IMPLEMENTASI TEORI MONOPOLI RICHARD A. POSNER TERHADAP UNDANG-UNDANG NOMOR 5 TAHUN 1999 TENTANG LARANGAN PRAKTIK MONOPOLI DAN PERSAINGAN USAHA TIDAK SEHAT - SULISTYOKO, ARIE (At-Taradhi Jurnal Studi Ekonomi, 2014)
The main problem in the domestic competition is not at a high level of market concentration, but artificial barriers to market competition created by government policies, such as giving high protection for companies that are well established in the market. There are two problems that must be concerned, namely the implementation of the Richard A. Posners monopoly theory of the Law Number 5 Year 1999 about the prohibition of monopolistic practices, unfair business competition, and how to interpret and enforce the Commission's Law Number 5 Year 1999. Antimonopoly Law gives the same opportunity and the freedom to all businessman to compete in the market. There are rules that must be obeyed by businessman, which may not act as he pleased in the conduct of his business and shall not commit unfair competition. The Antimonopoly Law is supervised by the KPPU, the KPPU has the dual task besides to create the discipline in the competition also serves to create and maintain a conducive climate for business competition.